Narrative-Based Interactive Multimedia in Islamic Religious Education: Reconstructing Learning Engagement among Generation Z - Rizki Pebrina; Ulvi Marta Vera; Susi Herawati; Ali Akbar (Yayasan Adra Karima Hubbi, 2026)
Background. The emergence of the Society 5.0 era has catalyzed fundamental shifts within the educational landscape, specifically challenging Islamic Religious Education (IRE) to evolve. Purpose. This study aims to analyze the utilization of narrative-based interactive multimedia within the context of Islamic Religious Education. Specifically, the research investigates how this specific medium relates to student learning engagement and its overall effectiveness in addressing the pedagogical needs of the digital era. Method. The research employed a quantitative descriptive method to evaluate the implementation of these digital tools. Data were systematically collected through questionnaires distributed to students and subsequently analyzed using descriptive statistical techniques to determine the perceived benefits and levels of engagement. Results. The findings indicate that students perceive narrative-based interactive multimedia as highly beneficial for the learning process. The integration of technology is significantly associated with increased interest, motivation, and comprehension of IRE materials. Conclusion. This study concludes that narrative-based interactive multimedia is a relevant and appropriate learning medium for Generation Z. By fostering higher student engagement and providing more engaging narratives, these tools serve as a vital resource for modernizing Islamic Religious Education in the digital era.